Younger, dissatisfied, and unhealthy - Relative age in adolescence - Luca Fumarco; Stijn Baert; Francesco Sarracino (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
We investigate whether relative age (i.e. the age gap between classmates) affects life satisfaction and health in adolescence. We analyse data on students between 10 and 17 years of age from the international survey 'Health Behaviour in School-Aged Children' and find robust evidence that a twelve-month increase in relative age (i.e. the hypothetical maximum age gap between classmates) i) increases life satisfaction by 0.168 standard deviations, ii) increases selfrated general health by 0.108 standard deviations, iii) decreases psychosomatic complaints by 0.072 standard deviations, and iv) decreases chances of being overweight by 2.4%. These effects are comparable in size to the effects of students' household socio-economic status. Finally, gaps in life satisfaction are the only ones to reduce with the increase in absolute age, but only in countries where the first tracking of students occurs at 14 years of age or later.
Keywords: C26; D04; I21; I24; I31; 330; Academic Settings; Adolescent Characteristics; Education Policy; Life-Satisfaction; Health Outcomes